Development of a high-resolution marine ecosystem model for predicting the combined impacts of ocean acidification and deoxygenation - Bernardo, Lawrence Patrick C.; Fujii, Masahiko; Ono, Tsuneo (Frontiers in Marine Science, 2023)
An approach was developed to help evaluate and predict the combined effects of ocean acidification and deoxygenation on calcifying organisms along the coast of Japan. The Coastal and Regional Ocean COmmunity (CROCO) modeling system was set up to couple the Regional Ocean Modeling System (ROMS) to the Pelagic Interaction Scheme for Carbon and Ecosystem Studies (PISCES) biogeochemical model and used to reproduce physical and biochemical processes in the area around Miyako Bay, Iwate Prefecture, Japan. Future scenario cases were also set up, which used initial and boundary conditions based on Future Ocean Regional Projection (FORP) simulations. Present day simulations were able to reproduce the general features of observed physical and biochemical parameters, except for some rapid decreases in salinity, pH and aragonite saturation state (Ωarag). This suggests that more local factors which have not been introduced into the model, such as submarine groundwater discharge, may be involved, or that river inputs may be underestimated. Results of the future projections suggest a significant impact of global warming and ocean acidification on calcifying organisms for the worst case of climate change under the Representative Concentration Pathway (RCP) 8.5 scenario. In particular, it is feared that values of Ωarag would approach the critical level for calcifying organisms (Ωarag< 1.1) throughout the year, under which decreased larval shell lengths and malformation have been observed experimentally for the locally grown Haliotis discus hannai (Ezo Abalone) species. However, these findings may not be true for a different coastal locality, and this study highlights and continues to stress the importance of developing model setups capable of incorporating both regional and local factors affecting ocean acidification and deoxygenation.